Penguatan Kompetensi Guru Sekolah Dasar melalui Model Pembelajaran Induktif dengan Alat Peraga Konsep Luas Bangun Datar - Aisah, Siti; Putri, Willa; Ilaika, Eka (EduInovasi: Journal of Basic Educational Studies, 2025)
Mathematics is an abstract concept and is built through deductive reasoning. These two factors make mathematics difficult for elementary school students to understand. Consequently, the process of learning mathematics presents a particular challenge for teachers. This Student Creativity Program (PKM) is a follow-up to previous research, which showed that students' understanding of the concept of area of a plane shape was as follows: 66% of students had a very poor understanding, 31% had a poor understanding, and 3% had a fairly good understanding. No students were able to fully understand the concept of area of a plane shape. This PKM aims to: 1) improve mathematics teachers' competence in understanding inductive learning models in mathematics, and 2) improve their ability to effectively use visual aids for the concept of area of a plane shape in inductive learning models. Both objectives are expected to impact the quality of students' understanding of basic mathematical concepts.